2021
DOI: 10.1038/s41598-021-84534-w
|View full text |Cite
|
Sign up to set email alerts
|

GWAS reveal a role for the central nervous system in regulating weight and weight change in response to exercise

Abstract: Body size and weight show considerable variation both within and between species. This variation is controlled in part by genetics, but also strongly influenced by environmental factors including diet and the level of activity experienced by the individual. Due to the increasing obesity epidemic in much of the world, there is considerable interest in the genetic factors that control body weight and how weight changes in response to exercise treatments. Here, we address this question in the Drosophila model sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…This suggests additional metabolic genes and pathways must contribute to sex differences in fat storage and breakdown ( Wat et al, 2020 ). Indeed, genome-wide association studies in Drosophila demonstrate sex-biased effects on fat storage for many genetic loci ( Nelson et al, 2016 ; Watanabe and Riddle, 2021 ). As evidence of sex-specific mechanisms underlying whole-body fat storage continues to mount, several reports have also identified male-female differences in phenotypes linked with fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests additional metabolic genes and pathways must contribute to sex differences in fat storage and breakdown ( Wat et al, 2020 ). Indeed, genome-wide association studies in Drosophila demonstrate sex-biased effects on fat storage for many genetic loci ( Nelson et al, 2016 ; Watanabe and Riddle, 2021 ). As evidence of sex-specific mechanisms underlying whole-body fat storage continues to mount, several reports have also identified male-female differences in phenotypes linked with fat metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is confirmed using the lifespan data from Ivanov and colleagues [37] (Pearson's product-moment correlation r = −0.065, p = 0.7202). Similarly, when we investigate the relationship between animal weight and climbing ability (data from [32]), we find no significant correlation in either sex, in control or exercise-treated animals (Pearson's product-moment correlation, p > 0.4). These findings suggest that high physical fitness, as measured by a climbing index, is not linked to either lifespan or animal weight in these Drosophila strains.…”
Section: The Relationship Between Climbing Ability Animal Activity Weight and Lifespanmentioning
confidence: 77%
“…We have shown that exercise induction with the TreadWheel leads to changes in activity levels in a sex-and genotype-dependent manner [31]. A 5-day exercise treatment with the TreadWheel induces changes in animal weight, again in a sex-and genotypedependent manner [32]. Thus, the Drosophila system is ideally suited to investigate the factors contributing to the variation in exercise response.…”
Section: Introductionmentioning
confidence: 99%
“…In Lymnaea stagnalis , changes in biophysical properties of isolated serotonergic neurons were discovered, as well as the involvement of volume neurotransmission in adaptation of the nervous system to physical exercise (Dyakonova et al, 2019 ). In Drosophila spp., in well controlled experiments with different regimes of training, the responsive neuronal genes and metabolic pathways are identified (Watanabe and Riddle, 2021 ); the role of octopaminergic system is evidenced in genetic, pharmacological and behavioral studies (Sujkowski et al, 2017 , 2020 ; Cobb et al, 2020 ). In the cricket G. bimaculatus , the most complete repertoire of behavioral changes produced by flying have been described in neuroethological investigations on aggression (Hofmann and Stevenson, 2000 ), mating (Dyakonova and Krushinsky, 2008 ), auditory orientation (Sergejeva and Popov, 1994 ; Mezheritskiy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This looks only as a temporal gap, as a number of neuronal genes and neuronal transcription regulators were reported recently to be affected by exercise in Drosophila spp. (Watanabe and Riddle, 2021 ).…”
Section: Insectsmentioning
confidence: 99%